Elaboración de un plan de marketing a la empresa padre e hijo en la ciudad de Nueva Loja - Yépez Carrasco, Patricia Emperatriz (2015)
This thesis project aims to develop a marketing plan for the company Father and Son, in the Province of Sucumbíos Lago Agrio Canton, same that would promote the development and growth of the company object of this study, which has been made based on theoretical underpinnings and field information obtained through the use of surveys of 222 customers, 3 employees and an interview with the manager. Within the research process is part of making a situational analysis of the company. Upon the user surveys and employees, the interview the manager and direct observation, gave us an overview of current business conditions and their environment. Based on the information obtained, data is set to develop Fortaleza, Weaknesses, Opportunities and Threats. Has developed the mission, vision and corporate values, as part of the administrative process for this has had the participation, cooperation and commitment of company employees by assisting customers, on the other hand the spread and implementation policies, objectives and strategies. Among the strengths of the company is determined to have its own financial capital and its main weakness not having a marketing plan, that's why the overall objective of this research is to design a marketing plan. By analyzing the EFE and EFI matrices, it is determined that the weighting factor is 2.70 EFE indicating that the company still does not take advantage of opportunities, and the threats which can harm you. Regarding the weighting factor EFI, a value 2.64 means that the company is in a favorable internal position, which ensures you can go ahead and develop positively in the medium was obtained. With internal and external analysis SWOT matrix that allowed me to define the opportunities, threats, strengths and weaknesses, so that the array of high impact with what we proceeded to perform the FO, DO, FA combination was built was built, DA resulting in the strategic objectives .: 1. Conduct an advertising plan to increase the dissemination of products and service offered by the company; 2. Implement technology to the administrative department; 3. Strengthen the departmentalization of the company; 4. Conduct a training plan for staff working in the company With the definition of the strategic objectives the "MARKETING PLAN NOW TO FATHER AND SON IN THE CITY OF NEW LOJA", the total cost for the workshop and warehouse Father and Son, be of $ 4,776.00 was made. Mimo that will help the company capture new customers, increase sales and generate higher returns to their